Some Physical Characteristics of the Enzymes of l-Tryptophan Biosynthesis in Higher Plants - Hankins, Charles N. (1976)
Anthranilate synthetase, phosphoribosyltransferase, phosphoribosyl anthranilate isomerase, and indoleglycerol phosphate synthetase were examined in partially purified extracts of the monocotyledon, Zea mays and the dicotyledon, Pisum sativum. The plant extracts were chromatographed on DEAE-cellulose and Sephadex G150. The molecular weights of the enzymes were determined and found to be similar to those observed for many bacteria. None of the plant tryptophan enzyme activities was aggregated in vitro as is also the case with most bacteria. This is in contrast with the complex aggregation patterns observed in other eucaryotic organisms that have been examined (fungi and Euglena gracilis). The tryptophan enzymes from peas and corn were generally similar but some differences in stability were observed.